Politics and popular culture - Street, John, 1952- (Cambridge, U.K. : Polity Press, 1997)
This book is divided into three parts: The Political and the Popular; Governing Global Culture; Political Theory/Cultural Theory.
Keywords: Culture; Politics; Politics and culture; Popular culture -- Political aspects